Pengaruh Latihan Yoga Surya Dharyam Terhadap Penurunan Tingkat Kecemasan Remaja di Pasraman Seruling Dewata Tabanan Bali - Ni Putu Indriani; Ni Kadek Surpi; Made G. Juniartha (UHN IGB Sugriwa Denpasar, 2022)
The anxiety rate in Indonesia is increasing every year, the prevalence of anxiety is estimated at 20% of the world’s population and 47,7% of adolescents feel anxious. Anxiety can be influenced by several factors incluiding family transmission, genetics, temperament factors, family and parental factors, life events, and cognitive detachment or social phobia. Yoga Surya Dharyam, which is an ancient Balinese ancient Watukaru Yoga Practice, is an exercise that aims to improve health. This study was fins out how the influence of Yoga Surya Dharyam practice on reducing adolescent anxiety levels at the Pasraman Seruling Dewata. The research method is quantitative with One-Group Pre-test Post-test design. The design of study with the experimental group was measured of observed before and after treatment. The research was conducted for 1 mont at the Pasraman Seruling Dewata involving 30 young women with an age range of 10 to 24 years. The independent variable (X) is Yoga Surya Dharyam and the dependent variable (Y) is the level of anxiety. Method of data collection using interview, observation, and measurement with a questionnaire. Data analysis using Paired Sample T-test. The data obtained are normal and homogeneous (parametric). The results of the output test in this study were 0.000 < 0.05 which indicated that there was an influence of Yoga Surya Dharyam on reducing adolescent anxiety levels. Yoga stimulates alpha waves in the brain which are linked to a state of deep relaxation. Yoga also increase the production of endorphins, which are anxiety hormones that also reduce anxiety.